2023
DOI: 10.3390/agronomy13112698
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Priming Effect of Abscisic Acid on Tolerance to Saline and Alkaline Stresses in Rice Seedlings

Zhonghui Feng,
Guanru Lu,
Miao Sun
et al.

Abstract: The plant hormone abscisic acid (ABA) regulates the plant response to environmental stress; therefore, ABA priming is an effective strategy for enhancing stress tolerance in rice. In this study, we investigated the priming effects of 1 and 5 µM ABA on the biochemical and physiological traits associated with seedling growth performance in two rice cultivars exposed to saline (100 mM NaCl) and alkaline (15 mM Na2CO3) stress via root drenching. ABA pretreatment effectively reduced damage in rice seedlings by miti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The MDA concentration can reflect the level of membrane lipid peroxidation and can thus indicate the degree of membrane damage under stress conditions [51]. It is usually enhanced with stress treatments [52,53]. In this study, the MDA concentration of I. typhifolia seeds exhibited a slight increase at T50, reaching its peak at T200.…”
Section: Effects Of Artificial Saline-alkali Stress On Seed Germinati...mentioning
confidence: 50%
See 1 more Smart Citation
“…The MDA concentration can reflect the level of membrane lipid peroxidation and can thus indicate the degree of membrane damage under stress conditions [51]. It is usually enhanced with stress treatments [52,53]. In this study, the MDA concentration of I. typhifolia seeds exhibited a slight increase at T50, reaching its peak at T200.…”
Section: Effects Of Artificial Saline-alkali Stress On Seed Germinati...mentioning
confidence: 50%
“…In response to saline-alkali conditions, plants typically close their stomata, a process that reduces water loss and serves as a survival strategy [66]. A previous study illustrated that gs is the most crucial photosynthesis parameter under abiotic stress [53]. In this study, the gs values of I. typhifolia all declined under artificial saline-alkali stress (T50-200 for over 7 d).…”
Section: Effects Of Artificial Saline-alkali Stress On Chlorophyll An...mentioning
confidence: 51%
“…Previous research has revealed that ABA serves as a key factor in improving the tolerance of rice seedlings to saline–alkaline stress, showing broad application prospects in agricultural practices and production [ 39 , 40 ]. However, issues such as high cost and photodecomposition limit the application.…”
Section: Introductionmentioning
confidence: 99%